Effects of surface charge of thin-film composite membrane on copper (II) ion removal by using nanofiltration and forward osmosis process. (February 2020) - Hamid, M.F.; Abdullah, N.; Yusof, N.; Ismail, N.M.; Ismail, A.F.; Salleh, W.N.W.; Jaafar, J.; Aziz, F.; Lau, W.J.
Graphical abstract: Highlights: TFCs with different surfaces charges were fabricated via interfacial polymerization. Excellent rejection by both positively and negatively charged TFC membranes. Double-layer assisted effect by negatively charged TFC on Cu (II) ion retention. Poor metal retention by mixed charged TFCs. Abstract: This study aimed to investigate the effects of cooperative membrane surface charge of thin film composite (TFC) membranes for removal of Cu(II) from aqueous solution using nanofiltration (NF) and forward osmosis (FO) process. A total of five composite membranes with different piperazine/polyethyleneimine (PIP/PEI) ratio (1.0-PIP, 0.3-PEI, 0.5-PEI, 0.7-PEI, 1.0-PEI) were fabricated and the physicochemical properties of these membranes were characterized using scanning electron microscope (SEM), attenuated total reflection -Fourier transform infra-red (ATR-FTIR), zeta potential and contact angle analysis. Physicochemical analysis confirmed the formation of polyamide (PA) layer for all TFC membranes. Result of zeta potential analysis revealed that 1.0-PEI is positively charged surface whereas 1.0-PIP is negatively charged. Consequently, 1.0-PEI exhibits higher flux compared to 1.0-PIP owing to its higher hydrophilicity. Interestingly, 1.0-PEI demonstrates the highest copper (Cu) (II) ion rejection of more than 95% and 99% in NF and FO operation respectively, outperforming the other produced TFCs. Result of the elemental diffraction x-ray (EDX) further explained that the copper rejection was facilitated by the cooperative surface charge.